Effect of collection methods of bovine ruminal fluid on ruminal and microbiological paramethers - de Oliveira, Mauro Dal Secco; Sampaio, Alexandre Amstalden Morais; Vieira, Paulo de Figueiredo; de Freitas, Julio Cesar Mestriner; Iturrino, Rubens Pablo Shock (Pesquisa Agropecuaria Brasileira, 1999)
An experiment was conducted to determine the effects of three methods of collection on volatile fatty acids concentrations, amoniacal nitrogen levels and protozoa number in ruminal fluid of bovine. Three methods of collection were used: manual, vacuum-pump and with a nasal-esophagic tube. It was used a completely randomized design with three treatments and five replications. The data showed that the nasal-esophagic tube method resulted in lower values of propionic acid, butiric acid, volatile fatty acids and amoniacal nitrogen in ruminal fluid. The total number of protozoa do not affected by the methods of fluid collection. The manual and the vacuum-pump method showed an indicated methods for the determinations of the studied parameters.